(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
The problems of reliability, stability and kinematics accuracy of domestic high-speed rapier loom are urgent to be solved. For the limitations of used methods of solving kinematics accuracy reliability, the mathematical solution model and index of kinematics accuracy reliability of beating-up mechanism were established based on the geometrical principle of reliability index. The particle swarm optimization was improved. Then using improved particle swarm optimization, the kinematics accuracy reliability of beating-up mechanism of high-speed rapier loom was optimized. The computational precision and effectiveness of solving are both improved. Thus a new valid method is provided for the solution of kinematics accuracy reliability of beating-up mechanism of high-speed rapier loom.